1997
DOI: 10.1111/1467-8330.00033
|View full text |Cite
|
Sign up to set email alerts
|

From a Geography of Labor to a Labor Geography: Labor's Spatial Fix and theGeography of Capitalism

Abstract: Mainstream neoclassical economic geography and its Marxist critique have largely failed to incorporate active conceptions of working class people in their explanations of the location of economic activities. Neoclassical approaches tend to conceive of workers simply as factors of location, whereas Marxist approaches primarily focus on how capital structures the economic landscape in its search for profit and frequently relegate labor to the status of “variable capital.” Both approaches present Geographies of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
236
0
30

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(268 citation statements)
references
References 71 publications
(44 reference statements)
2
236
0
30
Order By: Relevance
“…The longer the firm has been in this particular place, the harder it is to relocate out of this place without experiencing negative effects (e.g. Kessides, 1990;Cox and Mair, 1989;Herod, 1997). This 'spatial fix' strengthens forces of inertia.…”
Section: Locational Inertia and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer the firm has been in this particular place, the harder it is to relocate out of this place without experiencing negative effects (e.g. Kessides, 1990;Cox and Mair, 1989;Herod, 1997). This 'spatial fix' strengthens forces of inertia.…”
Section: Locational Inertia and Hypothesesmentioning
confidence: 99%
“…Therefore, it is expected that the spatial environment (or surroundings) of the firm partly determines the survival (getting older) of firms. As firms are located on the same spot longer, they create close ties with local suppliers, capital suppliers and customers (Hoogstra and van Dijk, 2004), also seen as spatial fix (Herod, 1997) and lock-in effects (Gulati et al, 2000). Creating these ties takes time and to break down these ties can be disastrous for the effectiveness of firms (Brouwer, 2005).…”
Section: Locational Inertia and Hypothesesmentioning
confidence: 99%
“…This same study (1999: 239) also concluded that, despite trade liberalization, the United States-Canadian border "imposes barriers to arbitrage comparable to 1,700 miles of physical space." Such observations reinforce the theoretical contributions made by radical economic geographers since the 1980s (Herod 1991(Herod , 1994(Herod , 1997(Herod , 1998(Herod , 2001Massey 1994;Harvey 1982Harvey , 1989Harvey , 2001Peck 1996;Smith 1984). Although these theorists are divided over the relative contributions of capital and labour to the construction of what Harvey (1982: 421) calls the "historical geography of capitalism," they are broadly united in conceiving the latter as "a social process" whereby "productive forces and social relations .…”
mentioning
confidence: 56%
“…I look not only at trade union sanctioned protest but also at non-union forms of resistance. As Herod (1997) has stated, whilst trade unions are certainly powerful workers' institutions, they do not hold a monopoly as instruments of the expression of workers' interests.…”
Section: Geographies Of Resistancementioning
confidence: 99%
“…The geographically situated and embedded nature of workers' lives and the spatiality of trade unionism is now clearly recognised and, amongst others, Andrew Herod's writings on the geographies of the labour process have demonstrated the shift to understanding the spatial strategies used by workers and trade unions and the ways in which they use and create space, actively shaping economic landscapes (Herod 1994(Herod , 1997(Herod , 1998(Herod and 2001. Indeed, a far greater engagement between geographers and industrial relations scholars has been called for (Herod 2002).…”
Section: Introductionmentioning
confidence: 99%